Health-Related Quality Of Life Of Patients With Unresectable Hepatocellular Carcinoma And Costeffectiveness Of The First-Line Treatments In A Medical University Hospital In Yunnan, China - Gong, Hongyu (2024)
In china, unresectable hepatocellular carcinoma (uhcc) poses a significant clinical challenge, highlighting the need to assess the cost-effectiveness and accessibility of first-line treatments. This study examined the cost-effectiveness of sorafenib, lenvatinib, and donafenib for uhcc in china, with a focus on disparities in quality-adjusted life years (qalys). We used a partitioned survival model for the analysis, drawing clinical data from medical records, patient-reported outcomes, literature, and expert consensus. Key outcomes included costs in us dollars, health outcomes in qalys, and the incremental cost-effectiveness ratio (icer) based on a willingness-to-pay threshold of us $37,128 (three times china's per capita gdp) per qaly gained. Sensitivity analyses were conducted to assess robustness. We also ran linear regression models to explore the relationship between qalys and variables such as treatment, age, gender, weight, job status, education, income, ethnicity, and chronic liver disease. Shapley values were used to determine the relative importance of these factors. Sorafenib provided an additional 0.024 qalys compared to lenvatinib, with icers of us $-176,876.12/qaly (weight >60 kg) and us $- 562,151.20/qaly (weight <60 kg). Negative icer values indicate that sorafenib is not only more effective but also less costly compared to lenvatinib, making it a dominant treatment option for both weight categories.